Antígona, teatro e psicodrama: uma experiência em preparação de atores - Vitagliano, Estéfano Martins (2015)
This work is the result of a qualitative action-research aimed to investigate the possibilities of the Psychodrama method, and mostly, Spontaneity Theater along with a processes of scenic preparation with a non-professional actors group. The process was developed during two months with a group of Pedagogy students proposing to act Sophocles' Antigona at the completion of the XI Week of Classical Studies of the College of Education of University of São Paulo. Within this proposal there was rehearsals using the principals of Classic Theater and, as a support to the actors, the Psychodrama method enters to provide a new perspective and a new look to the dramatic construction. The methodology and theoretical foundation that supports this research is centered in the Psychodrama writings of Moreno and his Spontaneity Theater, along with the techniques pertinent to the methods. In this foundation, attempted also the rescue of Greek Theater with the Aristotelian conceptions along with Sophocles, author of the play. The results points to what became the principal revelation with the actors preparation using the Psychodramatic proposal: the rescue of spontaneity-creativity manifested with the consciousness gathering of the actor in front of the impact in his subjectivity, with the text appropriation that ceased to be only memorized and became a self sponken language that sustains the character